Observations on the biology and behavior of the mite Macrodinychus sellnicki (Mesostigmata: Uropodidae), ectoparasite of the crazy ant Paratrechina fulua (Hymenoptera: Formicidae) - GONZÁLEZ-V., VICTORIA EUGENIA; GÓMEZ-L., LUIS ANTONIO; MESA-C., NORA CRISTINA (Revista Colombiana de Entomología, 2004)
The crazy ant Paratrechina fulva (Mayr) has conditions found in sugarcane adequate for establishing and proliferating, causing serious problems to growers. In 1996, the presence of a mite attacking crazy ant pupae was detected in Risaralda sugar mill; several investigations were conducted to elucidate its biology, behaviour other relationships between the mite and the ant, in order to determine the possibility of using the mite as a control agent of ant populations. The mite, identify as Macrodinychus sellnicki (Hirschmann), is a myrmecophile and develops as an ectoparasitoid sucking interna! fluids of the pupa, which in turn dies when the adult mite emerges. Percent parasitism by mites in the field may vary from O to 93%. Before becoming an adult M. sellnicki passes through three development stages: larva, protonymph and deutonymph. Mean duration of the life cycle was 30 days from active larva to emerged adult. After copulation, females formed eggs 7 days later and larvae 37 days later, suggesting ovoviviparity. Birth of larvae was not observed; these are active and seek their host. Nymphal stages have regressive development of their locomotion appendages. M sellnicki has a high capacity to affect P. fulva populations but its mass reproduction in laboratory was not possible. lts potential use therefore would be inoculative, consisting of liberations of highly parasitized individuals obtained from the field into areas where there are crazy ant outbreaks but the mite is absent.